The effects of hospice coverage on Medicare expenditures. - Kidder, D (1992)
This article reports on the findings of a study of the effects of the hospice program on Medicare Part A expenditures during the first three years of the program. The analysis compared treatment costs between hospice beneficiaries and nonbenefit patients with diagnosis of malignant cancer during their last seven months of life. It was estimated that during the first three years of the hospice program, Medicare saved $1.26 for every dollar spent on Part A expenditures. While the methodology included use of data from Medicare claims to adjust for confounding factors, including self-selection bias, our estimated savings might still have been overstated due to persistent selection effects. The extent of savings also varied according to the hospice's organization. Freestanding hospices, in contrast to those affiliated with either a hospital, nursing home, or home health agency, achieved the greatest savings by utilizing home care more extensively. However, we note that payment rates are increasing and the limits on the benefit period are being lifted, making it possible that the savings related to the hospice program found in this study will not continue. Of greater importance may be the long-term access and quality effects engendered by the benefit's preference for home care.